2005
DOI: 10.1681/asn.2005060666
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Burden of Cardiovascular Calcification in Patients with Chronic Kidney Disease

Abstract: Patients with chronic kidney disease (CKD) have a higher burden of atherosclerotic coronary artery disease compared with age-and gender-matched individuals with normal renal function. Cardiovascular calcification (CVC), a marker of atherosclerosis, is also more prevalent in these patients and is associated with serious clinical consequences. The pathogenesis of CVC is complex and includes factors that promote calcification and others that inhibit calcification. Thus, multiple therapeutic interventions should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 59 publications
3
28
1
Order By: Relevance
“…Notably, patients with chronic kidney disease (CKD) are at high risk of cardiovascular disease. 57 These patients often receive a high-calcium diet (to complex phosphate), vitamin D, and warfarin (to prevent thrombotic events). It was demonstrated, however, that each of these treatments is associated with an increased risk of arterial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, patients with chronic kidney disease (CKD) are at high risk of cardiovascular disease. 57 These patients often receive a high-calcium diet (to complex phosphate), vitamin D, and warfarin (to prevent thrombotic events). It was demonstrated, however, that each of these treatments is associated with an increased risk of arterial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…[93][94][95] A recent study showed that 40% of patients with CKD and a mean GFR 33 mL/min exhibited coronary artery calcification compared with 13% in matched control subjects with no renal impairment. 96 Calcification can be found in atherosclerotic plaques and in the vascular media, smooth muscle cells, and elastic laminae of large elastic and medium muscular arteries as well as in cardiac valves.…”
Section: Vascular Calcification Inducers and Inhibitors Of Calcificamentioning
confidence: 99%
“…96 Calcification can be found in atherosclerotic plaques and in the vascular media, smooth muscle cells, and elastic laminae of large elastic and medium muscular arteries as well as in cardiac valves. [93][94][95] Subjects with renal failure who exhibit medial calcification are typically middle-aged and have been dialyzed for some time, although some individuals may already have calcified vessels before dialysis. 97 There is a specific dialysis-related type of vascular calcification called calciphylaxis, or calcific uremic arteriopathy, that is characterized by diffuse calcification of the media of small to medium arteries and arterioles with intimal proliferation and thrombosis that results in skin ulcers 98 and can lead to life-threatening skin necrosis or acral gangrene.…”
Section: Vascular Calcification Inducers and Inhibitors Of Calcificamentioning
confidence: 99%
“…Increased vascular calcification has also been invoked in cardiovascular disease among patients with renal disease. 7 PROactive was a double-blind, randomized, placebocontrolled study that investigated the effect of pioglitazone, a peroxisome proliferator-activated receptor gamma (PPAR␥) activating thiazolidinedione, on a combined end point of vascular events. 4 In PROactive, the decline in the primary end point (approximately 10%) was not statistically significant.…”
mentioning
confidence: 99%